Some diagnostic defects and their causes in emergency cardiac care - Yu. D. Sergeev; Yu. V. Bisyuk (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To analyze diagnostic defects and to identify objective and subjective factors causing inadequate emergency cardiac medical care (ECMC). Material and methods. Two thousand medical histories of patients hospitalized with myocardial infarction (MI) and acute coronary syndrome, were analyzed. Results. Adverse outcomes were registered in 312 cases (15,6 %), including diagnostic defects in 83,3 %. The causes included inadequate doctor qualification (52,6 %), diagnostics and treatment inaccuracy (48,4 %), haste (44,6 %), or combination of inadequate qualification, inaccuracy, and specialist incompetence (34,6 %). Low doctor qualification resulted in inattentiveness (21,5 %) and uncertainty (19,6 %). Over-self-assurance (11,5 %), associated with underestimation of complaints, anamnesis, or clinical data, caused late MI and unstable angina diagnostics. Conclusion. Continuous analysis of ECMC defects, their causes and sources could improve ECMC quality and decrease the risk of legal actions initiated by patients and their relatives.